REPRODUCTIVE AND LIPID CYCLES IN THE ATYID PRAWN CARIDINA RAJADHARI (BOUVIER) - Victor, B (Indian Journal of Fisheries, 2011)
The atyid prawn Caridina rajadhari exhibited a continuous breeding cyclewith two distinct spawning seasons (October-November and February-March).Histological studies of adult females revealed a continuously active germinal zonewith different maturational stages of oocytes. The continuous spermatogenic activitywas evident from seasonally consistent gonad index values and successive wavesof various stages of sperm differentiation. Lipid was selectively localized in thetissues of C. rajadhari and was found to be increased in ovary and hepatopancreasduring spawning months. The lipid levels of testis were low, may be due to thedifference in relative size of gonad. The breeding rhythm of the prawn appears tofollow closely the monsoon season and greater food availability.